Kedudukan Organ Perseroan Perorangan Pada Usaha Mikro Kecil dan Menengah Pasca Berlakunya Undang-Undang Nomor 6 Tahun 2023 - Sayilendra Putra, Moody Rizqy; Bryan Joeliant, Hanz (UNES Law Review, 2023)
Many MSMEs in Indonesia are PT legal entities. MSMEs had a positive impact on the Indonesian economy that can't be separated from the presence of Law No.11/2020. This law introduces the concept of individual companies for MSMEs. After experiencing various dynamics, Job Creation Law finally changed to Law No. 6/2023. This research discusses the position of individual company organs in MSMEs in the New Job Creation Law which consists of one founder who is also the shareholder and director. There are inconsistencies in New Job Creation Law, but they can be solved using the principle "lex posterior derogat legi priori". Apart from that, the duties and responsibilities of individual company organs adhere to a one-tier board system which combines directors and commissioners. This normative legal research uses primary and secondary legal materials collected through library research and analysing with a statute and conceptual approach.